TH6.7 Direct Streaming of Acute Surgical Patients to an Advanced Nurse Practitioner-led Service: A Prospective Audit of a Pilot Service to Improve Patient Flow. (9th August 2022) - Riley, Anna; Aherne, Aileen; Box, Joe; Grady, Natalie; Maria, Jashmin; Chan, Anthony
Abstract: Aims: The ongoing uncertainty of the COVID-19 pandemic and recovery to re-establish elective services presents a major challenge to the NHS. Patient flow and bed capacity is now a priority for acute hospitals. We have implemented a new service model aimed at improving patient flow from A&E, where acute surgical patients are triaged and referred directly to the Advanced Nurse Practitioner (ANP) team for assessment and management. A criterion based on the presenting complaint and clinical observations was developed to identify suitable patients. The utilisation of this service was audited for its safety and impact on the Emergency General Surgical provision. Methods: The setting is a busy University Teaching Hospital with a diverse catchment population of 75, 000. A prospective audit identified the number of patients utilising the new care pathway and details of any adverse events or delays in treatment identified. All patients presenting with a General Surgical condition were included. Results: Between August and December 2021, 361 patients were referred directly from A&E (81% within first 2 hours of presentation) to the surgical ANP team for assessment. Of these, 85 (24%) were admitted for emergency treatment and 276 (76%) were discharged the same day for either ambulatory or outpatient follow-up, or back to Primary Care. There were no adverse events identified during the audit period. Conclusion: Direct streaming of acute surgical patients within a defined criteria to an ANP-led service is safe and effective in helping to improve patient flow and experience within an acute care model.